Low-energy electron-impact dissociative excitation of molecular hydrogen and its isotopologues - Scarlett, L.; Tapley, J.; Fursa, Dmitry; Zammit, M.; Savage, J.; Bray, Igor (American Physical Society, 2017)
We apply the adiabatic nuclei convergent close-coupling method to electron-impact dissociative excitation of H2 in the low-energy regime. Differential and integrated cross sections are presented for excitation of the bSu+3 state, the primary pathway t o dissociation of H2 at low energies. Agreement with experiment is satisfactory. Results are also presented for the isotopologues D2, T2, HD, HT, and DT, which show a pronounced isotope effect near threshold in both the differential and integrated cross sections.